Beyond burnout: A comprehensive investigation of burnout, resilience, and career continuity among Palestinian lawyers in a complex socio-political environment - Muayad K. Hattab; Noor Omar Adas; Abdalkarim Ayyoub; Shadi Khalil Abualkibash; Muntaser Nafeth Asmar; Akram Daoud; Ghassan Khaled; Zuheir N. Khlaif (PLoS ONE, 2025)
This article investigates burnout among lawyers and proposes systemic changes to reduce pressure and stress in the legal profession while enhancing resilience among lawyers. The article focuses on factors influencing career continuity among Palestinian lawyers within a socio-politically complex environment. It discusses elements contributing to resilience, including a positive mindset, a strong support system, training, and social support. The study reveals exceptional resilience among Palestinian lawyers. A quantitative cross-sectional study was used; the goals of the study involved 323 participants from different places in Palestine. Data analysis employed Smart PLS4 to build a regression model. Challenging conventional notions, the study provides valuable insights for state strategies, legal firms, educational institutions, and policymakers to address challenges and improve lawyer retention and job satisfaction in an environment marked by unstable economic and political conditions. Additionally, it examines gender-specific career intentions, notably women lawyers displaying a stronger inclination to stay, potentially linked to socio-economic responsibilities. This study contributes significantly to existing literature by providing a unique case study on career continuance determinants within economic and political instability. It sets a precedent for further study and strategic improvements in lawyer retention and job satisfaction within high-stress professions in an economically and politically complex environment.